Hong Kong in revolt : the protest movement and the future of China - Au, Loong Yu (Pluto Press, 2020)
"Hong Kong is in turmoil, with a new generation of young and politically active citizens shaking the regime. From the Umbrella Movement in 2014 to the defeat of the Extradition Bill and beyond, the protestors' demands have become more radical, and their actions more drastic. Their bravery emboldened the labour movement and launched the first successful political strike in half a century, followed by the broadening of the democratic movement as a whole. But the new generation's aspiration goes far beyond the political. It is a generation that strongly associates itself with a Hong Kong identity, with inclusivity and openness. This book sets the new protest movements within the context of the colonisation, revolution and modernisation of China."